Lifting the veil of accounting information under different accounting standards: lessons learned from the German experiment - Carmen Adamek; Christoph Kaserer (Technische Universität München, Center for Entrepreneurial and Financial Studies (CEFS), 2006)
It is well-known from US-related studies that investors systematically overreact to accrual-based accounting information. We address the question to what extent this accrual anomaly is related to different accounting standards. We provide empirical evidence that the accrual anomaly is also present in Germany. However, this anomaly has become particularly important after the year 2000 and cannot be detected for firms presenting their financial statements under German GAAP. It is argued that introducing true and fair view accounting, like IFRS, that relies on difficult-to-verify information, may not be suitable to improve accounting information quality in the context of a weak corporate governance system.
Keywords: 330; accrual anomaly; earnings persistency; conservative accounting; true and fair view accounting; accounting standards; accounting regulation; empirical accounting research; German GAAP; IFRS/IAS; US-GAAP; Jahresabschluss; Bilanzielle Bewertung; International Financial Reporting Standards; Bilanzpolitik; Geschäftsbericht; Deutschland